An Analysis of the Use of the Quizizz Application as a Learning Evaluation Tool in Pancasila Education Subject for Fifth Grade at SDN 09 Sitiung - Faradesi, Syahnaz; Hasibuan, Rusdi Indra; Nanda, Dodi Widia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the use of the Quizizz application as a learning evaluation tool in the Pancasila Education subject for fifth-grade students at SDN 09 Sitiung. The background of this research is the need for learning innovations that align with the Merdeka Curriculum, which allows teachers the flexibility to choose evaluation tools that suit the needs and characteristics of their students. One such innovation is the use of digital-based educational applications like Quizizz. This research employs a qualitative method with a case study approach and data collection through interviews. The research subjects include the fifth-grade homeroom teacher and all fifth-grade students at SDN 09 Sitiung. The results show that the use of Quizizz is effective as a learning evaluation tool. Quizizz not only assists teachers in preparing and distributing test questions but also provides students with an enjoyable learning experience through its interactive features and real-time feedback. The application also enhances students’ learning motivation and outcomes, as reflected in their enthusiasm during its use and improved evaluation scores. The advantages of Quizizz include easy access, an engaging interface, and instant feedback. However, there are some drawbacks, such as dependence on internet connectivity and limited question types. Thus, Quizizz can serve as an effective alternative to support digital-based learning evaluation at the elementary school level.